Intracytoplasmic Motile Sperm Selection in Fresh and Frozen Semen and its Correlation with Seminal Attributes of Kankrej Bull - F. Chaudhary, Karan; N. Suthar, Babulal; S. Suthar, Vishal; C. Nakhashi, Haresh; G. Joshi, Chaitanya (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Total 8 mature healthy Kankrej bulls (7 replicates) were selected for evaluation of seminal attributes at fresh and frozen stage of cryopreservation. Seminal attributes evaluated included sperm viability, acrosome integrity, HOST-EN test, intracytoplasmic motile sperm selection (IMSI) and sperm mucus penetration test (SMPT). Based on the nuclear abnormalities, sperms were classified in Grade I, II, III and IV. Per cent sperm viability, acrosome integrity, HOST- reacted sperm and Grade I sperm were found significantly lower in frozen semen as compared to fresh semen. Grade IV sperm as assessed by IMSI tool was found significantly higher in frozen semen as compared to fresh semen. Correlation study revealed significant and positive correlations of sperm viability with acrosome integrity and HOST, while significant negative correlation with grade IV sperm. Sperm viability and acrosome integrity were positively correlated with SMPT. Key words: Cryopreservation, IMSI, Kankrej bull, Semen, SMPT
Keywords: Cryopreservation; IMSI; Kankrej bull,; Semen; SMPT